Did the CPA Shut the Bathroom Doors for Transgender and Non-Binary People? A Critical Legal Reflection of Section 9(2) of the CPA - Tshepiso Scott-Ngoepe; Obakeng Van Dyk (Potchefstroom Electronic Law Journal)
The Consumer Protection Act 68 of 2008 (CPA) introduced a variety of consumer rights that are intended to protect consumers in their engagement with suppliers. Amongst these rights is the consumer's right to equality in the consumer market. Section 8 of the CPA sets out practices that are considered to be prohibited discriminatory marketing practices; while section 9 of the CPA provides instances that constitute reasonable grounds for differential treatment in certain circumstances. In particular, section 9(2) of the CPA provides that a supplier may provide and designate facilities that are separate but equal for the exclusive use of each gender. Alternatively, the supplier is permitted to offer access to a facility to one gender exclusively. Over the years, the LGBTQI+ community has increased awareness around gender stereotypes; and stressed that not all persons conform to a binary-gender allocation. Therefore, the question that arises is whether section 9(2) of the CPA, in permitting the designation of facilities to exclusively one gender, is unfairly discriminating against transgender and non-binary persons and is therefore unconstitutional. To the extent that the provision is constitutional, the paper considers whether the continued practice of having gender-segregated bathrooms to the exclusion of transgender and non-binary persons is constitutional.